Clinical profile and outcome of snakebite poisoning in sub-district hospital Akhnoor - Sharma, Chandan; Badyal, Ashima; Kumar, Sanjeev (International Journal of Advances in Medicine, 2021)
Background: In a predominantly agricultural country like India, with rich in flora and fauna, long rainy season and rural background, the encounter between man and snake is a frequent occurrence. Viper-bites are more common than other poisonous snakebites. Only the cases of snakebite with severe envenomation reach the health care centers. This study was planned to analyze the presentation of complaints and symptoms in snake bite patients. Methods: This ‘record based descriptive observational study’ was carried out over a period of 6 months from May 2020 to November 2020 in Sub District hospital Akhnoor. A total of 96 patients with a history of snake bite and signs of envenomation were included in this study. Results: Incidence was higher among people from rural background (86.46%), more among males (67.71%) and highest among farmers (53.13%) and labourers (16.67%). Maximum no of snakebites took place during night and on the lower parts of body, mainly legs (54.17%); while the period of the study contained the peak rainy season of the region. As many as 39.58% of victims didn’t receive any kind of formal first aid at all and as many as 48.96% patients reported after a minimum delay of 6 hours, which could be considered as potentially fatal. Chief complaints among the reported patients of snake bite were found to be: Local edema, bleeding, vomiting, drowsiness, ptosis and Ophthalmoplegia. Conclusions: There is an urgent and dire need for awareness and education among rural population about the hazards involved and treatment of snakebite.